2018
DOI: 10.1080/15389588.2017.1407924
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of alcohol impairment and odds of a driver injury or fatality in on-road farm equipment crashes

Abstract: Objective.-To estimate the prevalence of alcohol impairment in crashes involving farm equipment on public roadways and the effect of alcohol impairment on the odds of crash injury or fatality.Methods.-On-road farm equipment crashes were collected from four Great Plains state Departments of Transportation during 2005-2010. Alcohol impairment was defined as an involved driver having blood alcohol content of ≥0.08g/100ml or a finding of alcohol-impaired as a driver contributing circumstance recorded on the police… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Rural roads are different in their design to other roads [29]; generally, these roads have large shoulders and no line markings, making them non-uniform. It was acknowledged that elements of the road design and the relative size of LAVs are two factors that increase the level of risk from LAVs being present on roads.…”
Section: Discussionmentioning
confidence: 99%
“…Rural roads are different in their design to other roads [29]; generally, these roads have large shoulders and no line markings, making them non-uniform. It was acknowledged that elements of the road design and the relative size of LAVs are two factors that increase the level of risk from LAVs being present on roads.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys on alcohol and drugs on drivers provide valuable information on abuse patterns and trends, which help to establish new examination methods and legal limits as well as preventative measures. Numerous surveys on driving under the influence of alcohol and drugs were conducted worldwide through analyzing data from traffic offences and accidents as well as from roadside testing [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ]. The surveys revealed that in addition to alcohol, drugs including cannabis, amphetamines and cocaine were frequently taken by the drivers, while polydrug uses were not rare.…”
Section: Surveillance In Toxicologymentioning
confidence: 99%